2018
DOI: 10.1159/000489622
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1 Promotes Myocardial Angiogenesis in the Rat Model of Diabetic Cardiomyopathy

Abstract: Background/Aims: Microvascular insufficiency takes a critical role in the development of diabetic cardiomyopathy (DCM). So this study was designed to investigate the effects of Neuregulin-1 (NRG-1) treatment on myocardial angiogenesis and the changes of VEGF/Flk1 and Ang-1/Tie-2 signaling in the rat model of DCM. Methods: Diabetic rats were induced by a single intraperitoneal injection of Streptozotocin. 12 weeks after the diabetes induction, the rats with NRG-1 treatment were treated with tail vein injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…13) In addition, NRG-1 has been shown to promote myocardial angiogenesis in the ischemic and diabetic myocardium and is involved in the vascular endothelial growth factor (VEGF) / Angiopoietin-1(Ang-1) angiogenesis signaling events. 11,14,15) These findings revealed that NRG-1 might participate in the development of CCC and could function as a potential biomarker. However, the association between NRG-1 and CCC has not been explored in CAD patients.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…13) In addition, NRG-1 has been shown to promote myocardial angiogenesis in the ischemic and diabetic myocardium and is involved in the vascular endothelial growth factor (VEGF) / Angiopoietin-1(Ang-1) angiogenesis signaling events. 11,14,15) These findings revealed that NRG-1 might participate in the development of CCC and could function as a potential biomarker. However, the association between NRG-1 and CCC has not been explored in CAD patients.…”
mentioning
confidence: 69%
“…22,23) In diabetic cardiomyopathy, NRG-1 treatment can significantly promote myocardial angiogenesis and preserve cardiac function. 11) The mechanisms of the positive angiogenesis role for NRG-1 can be partly attributed to the elevated expression of VEGF and Ang-1. 11) However, another study has revealed that the expression and release of NRG-1 were significantly increased in human cardiac microvascular endothelial cells under VEGF and Ang-1 stimulation, which suggested that these angiogenic factors could regulate NRG-1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NRG-1 induces the growth of vascular endothelial cells in vitro in a manner independent of VEGF [ 103 ]. NRG-1 treatment reverses diabetic vascular injury by increasing myocardial capillary density and increasing myocardial blood flow in mice [ 104 ]. In ischemic injury, NRG-1 treatment increases capillary density within the peri-infarct region [ 83 ].…”
Section: Neuregulin In Repair Of Systolic Heart Failurementioning
confidence: 99%
“…The recent discovery of Nrp1’s dimerization of ErbB2 did not test NRGs ability to induce angiogenesis but further supports ongoing investigation into the ErbB-dependent regulation of angiogenesis. NRG-1 induces increased production and release of VEGF by endothelial cells in vivo [ 104 ]. However, in an in vivo model of corneal angiogenesis, NRG-1 induces angiogenesis independent of VEGF, suggesting that NRG is functionally angiogenic.…”
Section: Neuregulin In Repair Of Systolic Heart Failurementioning
confidence: 99%